CINAHL and MEDLINE: a comparison of indexing practices. - Brenner, S H (1989)
A random sample of fifty nursing articles indexed in both MEDLINE and CINAHL (NURSING & ALLIED HEALTH) during 1986 was used for comparing indexing practices. Indexing was analyzed by counting the number of major descriptors, the number of major and minor descriptors, the number of indexing access points, the number of common indexing access points, and the number and type of unique indexing access points. The study results indicate: there are few differences in the number of major descriptors used, MEDLINE uses almost twice as many descriptors, MEDLINE has almost twice as many indexing access points, and MEDLINE and CINAHL provide few common access points.